PENINGKATAN KEMAMPUAN MENGANALISIS INFORMASI DALAM TEKS EKSPLANASI MENGGUNAKAN MODEL PEMBELAJARAN DISCOVERY LEARNING SISWA KELAS XI SMK NEGERI 2 KOTA SORONG - Irwan Soulisa; Novalina Asmuruf; Frenny Silvia Pormes (LPPM Politeknik Saint Paul Sorong, 2023)
Increasing Ability to Analyze Information in Explanatory Text Using the Discovery Learning Learning Model for Class XI-Beauty Students at SMK Negeri 2 Kota Sorong. Formulation of the problem How to increase the ability to analyze information in explanatory text using the Discovery learning learning model for class XI students of SMK Negeri 2 Sorong city?. The purpose of the research is to find out the increase in the ability to analyze information in explanatory texts using the Discovery learning learning model for class XI students of SMK Negeri 2 Sorong City. The form of this research is classroom action research. The research subjects were 15 students of class XI-Beauty at SMK Negeri 2 Sorong City. The method used is a qualitative - quantitative description method. The research includes two cycles. Each cycle consists of planning, action, observation, and reflection stages. Data collection was carried out by tests and nontes. Data collection tools include observation guidelines, journals, interview guidelines, and photo documentation guidelines. It can be concluded as follows: There was an increase in the ability to analyze explanatory text using the Discovery learning learning model with non-test results in cycle I and cycle II covering two aspects, namely (1) Function (2) Completeness of General Explanation Structure, Process, Closing. The increase in the ability to analyze explanatory text is known from the results of cycle I and cycle II. The average value of the ability to analyze explanatory text is known from the results of cycle I. The average value of ability to analyze explanatory text in cycle I was 76% or in the less category, and experienced an increase in cycle II to 81.6% or in the good category. This shows an increase in the average value of writing the text of the observation report from cycle I to cycle II of 5.6%. In cycle II, using the Discopery Learning learning model, the number of students is 15 with a minimum average score that has been fulfilled, which exceeds the KKM score of 75.